Socio-cultural factors favoring home delivery in Afar pastoral community, northeast Ethiopia: A Qualitative Study - Mohammed Ahmed; Meaza Demissie; Alemayehu Worku; Araya Abrha; Yamane Berhane (BMC, 2019)
Abstract Background Despite expanding the number of health facilities, Ethiopia has still the highest home delivery services utilization. Health care service utilization varies between regions within the country. This study explored the socio-cultural factors influencing health facility delivery in a pastoralist region of Afar, Ethiopia. Methods An explorative qualitative study was conducted in October-December 2015. A total of 18 focus group discussions were conducted separately with mothers, male tribal leaders and religious leaders. In addition, 24 key informant interviews were conducted with Women's Affairs Bureau and district health office experts and traditional birth attendants and all were selected purposively. Data were coded and categorized using open code software and analyzed based on a thematic approach. Results The social factors that affect the choice of delivery place include workload, lack of independence and decision-making power of women, and lack of substitute for childcare and household chores during pregnancy and childbirth. The cultural and spiritual factors include assuming delivery as natural process ought to happen at home, trust in traditional birth attendants, traditional practices during and after delivery and faithful to religion practice, besides, denial by health facilities to benign traditional and spiritual practices such as prayers and traditional food preparations to be performed over there. Conclusion Socio-cultural factors are far more than access to health centers as barriers to the utilization of health facilities for child birth. The provision of a maternity waiting home around the health facilities can alleviate some of these socio-cultural barriers.